Bahasaku Bahasamu: Eksplorasi Bahasa Anak Muda Zaman Now - Rahma Allya Riady; Nesti Yusmia Rahma; Bagastya Fikriansyah Ramadhan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This article discusses the phenomenon of language use by young people in the contemporary era. Through qualitative research combining pragmatic and sociolinguistic theories, we explore various aspects of the language used by young people today. The language used by young people today is a reflection of cultural changes and social trends that affect the way they communicate.In this article, we outline the variety and creativity found in youth language, including the use of slang words, popular terms. Our analysis includes the social context that drives the development of this language, as well as its impact on youth understanding and identity. In addition, the article discusses the potential positive and negative impacts of the evolution of youth language on interpersonal communication and how this language reflects changing values in society. In an effort to understand and appreciate the dynamics of youth language, we invite readers to reflect on the importance of language adaptation in keeping up with the times.